Oxidative stress assessed in saliva from patients whit acute myocardial infarction: a preliminary study - Rubio, María Cristina (2013)
There is evidence that acute myocardial infarction (AMI) is associated with increasing production of reactive oxygen species and tissue injury. The aim of this study was to assess the presence of oxidative stress indices in saliva 24 and 48h after AMI. Materials and methods: We designed a prospective study comparing salivary levels of biomarkers of oxidative stress in patients with AMI with elevation of the ST segment in electrocardiogram versus clinically healthy subjects. Oxidative stress indices including the rate of oxidation of 2'7' dichlorohydrofluorescein diacetate (DCFHDA) and the activity of the antioxidant enzyme catalase (CAT) were evaluated in saliva from patients with AMI at 24 and 48 hours. At each sampling time, blood was drawn for serum markers of myocardial infarction. Results: This study included ten patients with acute ST-segment elevation myocardial infarction and ten clinically healthy controls. Mean age was 67.8 } 11.1 vs. 48.7 } 4.1 years (p<0.001) and gender was 60% male vs. 50% (p>0.05) for AMI vs. controls, respectively. Our results demonstrated an increase in the rate of oxidation of DCFH-DA in the myocardial infarction group as compared with controls (p=0.004), which remained unchanged at 48h. There was no difference in salivary catalase activity between controls and AMI subjects at 24h or at 48h post-diagnosis (p=0.157). The relationship between CAT48 and DCFH-DA48 was fairly significant (r=0.39; p=0.053). Conclusion: This preliminary study showed that biomarkers of oxidative stress are detectable in saliva of patients with acute myocardial infarction. Clinical Relevance: Future studies using a larger population are needed to confirm these observations and to explore the possibility of using the saliva to monitor evolving diagnosis and prognosis in acute coronary syndrome.